2019
DOI: 10.1039/c8an02426j
|View full text |Cite
|
Sign up to set email alerts
|

A multi-analytical approach for the study of red stains on heritage marble

Abstract: Red stains are a common discolouration on stone cultural heritage all over the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Studies carried out by micro-Raman spectroscopy showed the presence of minium (Pb 3 O 4 ), which confirmed the inorganic substance [8]. Subsequently, a series of research shows that red discoloration critically depends on the environment bacteria, decorate pigment, and human intervention [9]. The chromatic alteration process includes three parts: (a) enzymatic decolorization of bacterial pigments [10], (b) atmospheric attack of lead building components [11], and (c) production of hematite through washing and leaching of alkaline silicates [12].…”
Section: Introductionmentioning
confidence: 78%
“…Studies carried out by micro-Raman spectroscopy showed the presence of minium (Pb 3 O 4 ), which confirmed the inorganic substance [8]. Subsequently, a series of research shows that red discoloration critically depends on the environment bacteria, decorate pigment, and human intervention [9]. The chromatic alteration process includes three parts: (a) enzymatic decolorization of bacterial pigments [10], (b) atmospheric attack of lead building components [11], and (c) production of hematite through washing and leaching of alkaline silicates [12].…”
Section: Introductionmentioning
confidence: 78%
“…In the Table 2 the mineralogical, petrographic, and isotopic features of white and veined marbles are reported. Previous research, consisting of a multi-analytical approach for the study of the presence of red discouloration on the white marble of the external cladding of the Bapstistery, pointed out that the red staining is due to the presence of minium (lead tetraoxide) concentrated prevalently in the calcite crystal boundaries [26].…”
Section: Marblesmentioning
confidence: 99%
“…All mortar samples suffered a strong recrystallization of the binder in the form of spathic calcite. In different depths of S5, some differences in the aggregate characteristics were present: S5 (7-12) cm was composed of abundant binder/aggregate (B/A 1/3) and fine grain size predominant, while S5 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) cm and S5 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) cm were characterized by less binder/aggregate (B/A 1/2-1/3), and a fine-medium size was predominant (Figure 9e). Furthermore, a different amount of carbonate rock fragment was registered, with respect to the attic mortar samples (a higher entity in S5 samples).…”
Section: Mortarsmentioning
confidence: 99%
See 2 more Smart Citations